2018
DOI: 10.1097/jdn.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations and Management of Difficult-to-Treat Psoriasis

Abstract: Psoriasis is a common, immune-mediated skin disorder that can manifest as multiple clinical phenotypes. Although psoriasis affecting the scalp, face, nails, palms, soles, and intertriginous regions has not been studied as extensively as chronic plaque psoriasis in other body areas, these phenotypes can be associated with significant physical, psychosocial, and functional impairments, which impact quality of life. In addition, recent evidence has shown that psoriasis affecting these areas is more prevalent than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…The estimated incidence of scalp psoriasis among psoriatic patients is 45–56% of [3]. In one epidemiological study it was found that up to 90% of psoriatic patients may have the scalp affected by the disease at some point during their lifetimes [4, 5].…”
Section: Scalp Psoriasismentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated incidence of scalp psoriasis among psoriatic patients is 45–56% of [3]. In one epidemiological study it was found that up to 90% of psoriatic patients may have the scalp affected by the disease at some point during their lifetimes [4, 5].…”
Section: Scalp Psoriasismentioning
confidence: 99%
“…More than 70% of these patients report difficulty with everyday activities. Patients often experience the feeling of shame, embarrassment or self-consciousness about their scalp lesions and as a consequence wear hats or grow their hair long to hide the defect [4, 6].…”
Section: Scalp Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…9 Incidence of scalp psoriasis varies from 50% to 90%. 10,[11][12][13] Scalp manifestations may be the only sign or part of generalized plaque psoriasis along with focus elsewhere on the body. Genetic predisposition and environmental factors play a vital role in the incidence of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis has a variety of different presentations ( 8 ) , characterized by red plaques with adherent silvery-white scales, and typically has symmetrical distribution across the body ( 9 ) . Topical treatments are generally used as first-line therapy for most types of psoriasis ( 10 ) , which generally provide a high efficacy-to-safety ratio ( 11 ) . Moderate-to-severe psoriasis is usually treated with systemic therapies, such as methotrexate (MTX) or biologics ( 12 ) .…”
Section: Introductionmentioning
confidence: 99%